2021
DOI: 10.1111/add.15380
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of incentive salience from a first‐order alcohol cue to a novel second‐order alcohol cue among individuals at risk for alcohol use disorder: electrophysiological evidence

Abstract: Background and aimsIn susceptible individuals, cues associated with drug use are theorized to take on incentivemotivational properties, including the ability to reinforce higher-order, drug-related associative learning. This study aimed to test this prediction among people varying in risk for alcohol use disorder. Design, setting and participants Repeatedmeasures experiment with a measured individual difference variable at a University psychology laboratory in Missouri, USA. One hundred and six young adults (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 85 publications
4
21
0
Order By: Relevance
“…Enhanced ACR-P3 is associated with heavier and more hazardous alcohol use (Herrmann et al, 2001;Kroczek et al, 2018;Petit et al, 2013) as well as lower self-reported sensitivity to the acute effects of alcohol (Bartholow et al, 2007(Bartholow et al, , 2010, especially its sedative-like effects (Martins et al, 2019). Lower sensitivity to alcohol itself is associated with heavier and more hazardous alcohol use including use-related negative consequences and alcohol use disorder (AUD) symptoms (Bailey & Bartholow, 2016;Bartholow et al, 2007Bartholow et al, , 2010Davis et al, 2021;Fleming & Bartholow, 2014;Fleming et al, 2021;Hone et al, 2017;Martins et al, 2019;Trela et al, 2016), providing converging evidence for the association between enhanced ACR-P3 and AUD risk. Enhanced ACR-P3 also predicts heavier alcohol use prospectively (Bartholow et al, 2007) and differentiates individuals with AUD from those without (Namkoong et al, 2004).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Enhanced ACR-P3 is associated with heavier and more hazardous alcohol use (Herrmann et al, 2001;Kroczek et al, 2018;Petit et al, 2013) as well as lower self-reported sensitivity to the acute effects of alcohol (Bartholow et al, 2007(Bartholow et al, , 2010, especially its sedative-like effects (Martins et al, 2019). Lower sensitivity to alcohol itself is associated with heavier and more hazardous alcohol use including use-related negative consequences and alcohol use disorder (AUD) symptoms (Bailey & Bartholow, 2016;Bartholow et al, 2007Bartholow et al, , 2010Davis et al, 2021;Fleming & Bartholow, 2014;Fleming et al, 2021;Hone et al, 2017;Martins et al, 2019;Trela et al, 2016), providing converging evidence for the association between enhanced ACR-P3 and AUD risk. Enhanced ACR-P3 also predicts heavier alcohol use prospectively (Bartholow et al, 2007) and differentiates individuals with AUD from those without (Namkoong et al, 2004).…”
mentioning
confidence: 95%
“…Recently, there has been growing interest in the possibility that enhancement of various ERP components elicited by alcohol and drug-related cues could index risk that is more specific to alcohol and drug use. In particular, researchers have focused on neurocognitive processes related to the salience of alcohol and drug-related cues , such as selective attention (e.g., Dickter et al, 2014;Kroczek et al, 2018;Petit et al, 2012;Shin et al, 2010) and incentive-motivational value (e.g., Deweese et al, 2018;Dunning et al, 2011;Fleming et al, 2021;Garland et al, 2019;Minnix et al, 2013;Piasecki et al, 2017). Of special interest are the P3 and LPP components, established over half a century of work in experimental psychophysiology as indicators of extrinsic and intrinsic incentive-motivational value attributed to the eliciting stimulus (e.g., Begleiter et al, 1983;Codispoti et al, 2021;Deweese et al, 2016;Franken et al, 2011;Schindler & Straube, 2020;Schupp et al, 2000; for review, see: Hajcak & Foti, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying alcohol-use phenotypes associated with susceptibility to incentive salience sensitization (ISS) is an important translational goal. Evidence from both rodents (e.g., Beckstead & Phillips, 2009;Murphy et al, 2002;Risinger et al, 1994) and humans (see Cofresí et al, 2019Cofresí et al, , 2021Fleming et al, 2021) suggests low sensitivity (LS) to alcohol's acute effects (i.e., requiring a larger dose to experience various effects)a heritable, biobehavioral trait (Heath et al, 1999;Ray, Miranda, et al, 2010;Viken et al, 2003) linked to increased AUD risk (e.g., Schuckit, 1994; also see King et al, 2014King et al, , 2021, for evidence that higher sensitivity to alcohol's stimulating effects predicts AUD onset)-as a promising candidate phenotype associated with ISS susceptibility.…”
mentioning
confidence: 99%
“…Two recent studies tested this idea. In a sample of underage drinkers, Fleming et al (2021) found that exposure to This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
mentioning
confidence: 99%